Civil maintenance works in Wisma SESB building / Hazree Husin - Husin, Hazree (2015)
During the practical training at Sabah Electricity Sdn Bhd, which is located in Wisma SESB, Jalan Tunku Abdul Rahman, 88673 Kota Kinabalu, Sabah, the department that I’ve been posted to is Unit Senggaraan Bangunan Wisma SESB that is being led by En Ahmad Syazwan as a Chief of Unit. The position that I was entrusted to was as an Assistant Engineer . The case study that had been chosen as a practical report is Civil Maintenance Works in Wisma SESB Building. The Unit Senggaraan Bangunan is responsible in maintaining the Wisma SESB building. The building is a ninestorey office building. The Unit Senggaraan Bangunan of Wisma SESB will only do the minor repair works on the building with the help of the technicians. They would appoint any contractor or out-source company for major maintenance works that need specialized skills. The maintenance of the Wisma SESB building requires maintenance management, planning and programming. This is to ensure the maintenance works on the building to be smooth and effective.